Foundations of supply-side economics : theory and evidence - Canto, Victor A.; Joines, Douglas H.; Laffer, Arthur B. (New York : Academic Press, 1983)
The book represents the first compilation of paper specifically designed to illustrate the theory underlying supply-side economics.
Includes bibliographical references and index.
gp 22/01/2019
Loans
Keywords: Supply-side economics